MOF-based derivative composite photocatalyst as well as preparation method and application thereof

The preparation of MOF-based derivative composite photocatalysts through calcining, quenching and reduction treatments has solved the problems of complex preparation methods and low antibiotic degradation rate in the prior art, and achieved efficient antibiotic degradation effect.

CN119793451APending Publication Date: 2025-04-11ZHAOQING UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510026287.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing MOF-based derivative composite photocatalysts have complex preparation methods, harsh reaction conditions, and low antibiotic degradation rate.

Method used

By calcining the MOF, a MOF-derived material was obtained, and then quenched in a soluble metal salt solution, and finally a reduction treatment was performed to obtain a MOF-based derivative composite photocatalyst. The method is simple and the reaction conditions are mild, which improves the antibiotic degradation rate.

Benefits of technology

The efficient degradation of antibiotics was achieved. The degradation rate of tetracycline hydrochloride under ultraviolet light 365nm irradiation reached 97%, the mineralization rate reached 95%, and the reaction rate was 2.75 times that of the original TiO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005232803430000011
    Figure HDA0005232803430000011
  • Figure HDA0005232803430000012
    Figure HDA0005232803430000012
  • Figure HDA0005232803430000013
    Figure HDA0005232803430000013
Patent Text Reader

Abstract

The invention provides an MOF-based derivative composite photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of photocatalysts. The MOF is quenched in the soluble metal salt solution after being calcined, the MOF derivative material formed through calcination can be rapidly cooled through quenching, a large number of defects are formed on the surface of the MOF derivative material, on one hand, the number of oxygen vacancies can be increased through the defects, and the oxygen vacancies are beneficial to electron transmission and improvement of the catalytic effect; on the other hand, the metal loading capacity can be improved, the binding force between the MOF derivative material and the metal is high, the MOF derivative material is not prone to falling off, and the photocatalyst has good stability. According to the method, metal ions can be promoted to be reduced to form metal simple substances or metal clusters through reduction treatment, and the metals can generate heat when being used as the photocatalyst, so that oxygen vacancies and the metals generate light-heat effect for concerted catalysis, and the degradation effect of the photocatalyst on antibiotics is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a MOF-based derivative composite photocatalyst and a preparation method and application thereof. Background Art

[0002] With the vigorous development of modern medical technology and the rapid development of commercial economy, the use of antibiotics is becoming more and more frequent. However, antibiotic residues in water bodies can pose a potential threat to environmental safety even at low concentrations. Therefore, there is an urgent need to find effective methods to deal with antibiotic residues. Photocatalytic technology, as an advanced oxidation technology, has the advantages of almost complete degradation and simple operation. It is a green technology for treating antibiotic wastewater. Among them, TiO2, ZnO, WO3 and CdS are the most commonly used semiconductor nanomaterials for the treatment of antibiotics in wastewater due to their good optical and photocatalytic properties.

[0003] Metal-organic frameworks (MOFs), with their rich metal ions and organic ligands, have become ideal templates or precursor materials for the preparation of semiconductor nanomaterial photocatalysts. Based on the synthesis route of the original MOF template, the resulting catalyst can inherit and retain the unique pore structure of the original MOF. These characteristics greatly increase the number of exposed active centers. At the same time, its porous structure effectively promotes the adsorption and rapid transfer of reactant molecules, thereby improving the catalytic efficiency. However, the high recombination rate of photogenerated electron-hole pairs leads to less than ideal photocatalytic performance of semiconductor nanomaterials. By loading metals on the MOF surface, the metal nodes highly uniformly dispersed in the MOF framework can participate in the photocatalytic reaction as independent active sites, thereby greatly improving the atomic utilization efficiency of the metal nodes and improving the catalytic activity of the photocatalyst.

[0004] At present, the main method of loading metals on the surface of MOF is to mix the metal with the MOF precursor, and then perform hydrothermal reaction and high-temperature calcination to anchor the metal in the framework of MOF. However, this method has problems such as complex preparation method, harsh reaction conditions and low antibiotic degradation rate. Therefore, it is urgent to provide a method for preparing a MOF-based derivative composite photocatalyst with a simple method, mild reaction conditions and high antibiotic degradation rate. Summary of the invention

[0005] The purpose of the present invention is to provide a MOF-based derivative composite photocatalyst and a preparation method and application thereof. The method provided by the present invention is simple and the reaction conditions are mild. The obtained MOF-based derivative composite photocatalyst has a high degradation rate for antibiotics.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a MOF-based derivative composite photocatalyst, comprising the following steps:

[0008] (1) calcining the MOF to obtain a MOF-derived material;

[0009] (2) quenching the MOF derivative material obtained in step (1) in a soluble metal salt solution to obtain a MOF derivative material loaded with metal ions;

[0010] (3) The metal ion-loaded MOF-derived material obtained in step (2) is subjected to reduction treatment to obtain a MOF-based derived composite photocatalyst.

[0011] Preferably, the MOF in step (1) comprises one or more of a Ti-based metal organic framework material, a Co-based metal organic framework material, a Ni-based metal organic framework material, a Fe-based metal organic framework material and a Mn-based metal organic framework material.

[0012] Preferably, in step (1), the calcination temperature is 400-500° C.; the calcination time is 1-3 hours; and the calcination atmosphere is air.

[0013] Preferably, the soluble metal salt in the soluble metal salt solution in step (2) includes one or more of palladium chloride, silver nitrate, chloroauric acid, platinum nitrate, nickel nitrate and copper nitrate.

[0014] Preferably, the concentration of the soluble metal salt solution is 0.25-1 mmol / L.

[0015] Preferably, the temperature of the soluble metal salt solution during the quenching treatment in step (2) is 0 to 20° C.; and the quenching treatment time is 1 to 5 minutes.

[0016] Preferably, the temperature of the reduction treatment in step (3) is 200-300° C.; the time of the reduction treatment is 2-4 hours; and the atmosphere of the reduction treatment is a mixture of hydrogen and nitrogen.

[0017] The present invention also provides a MOF-based derivative composite photocatalyst prepared by the preparation method described in the above technical solution, comprising a MOF-derived material and a metal loaded on the MOF-derived material.

[0018] Preferably, the mass percentage of the metal in the MOF-based derived composite photocatalyst is 0.5-2%.

[0019] The present invention also provides the use of the MOF-based derivative composite photocatalyst described in the above technical solution in treating wastewater containing antibiotics.

[0020] The present invention provides a method for preparing a MOF-based derivative composite photocatalyst, comprising the following steps: calcining MOF to obtain a MOF-derived material; quenching the MOF-derived material in a soluble metal salt solution to obtain a MOF-derived material loaded with metal ions; reducing the MOF-derived material loaded with metal ions to obtain a MOF-based derivative composite photocatalyst. The present invention decomposes MOF into a MOF-derived material with a porous structure by calcination. The present invention quenches the MOF-derived material in a soluble metal salt solution, and during the quenching process, the MOF-derived material at a high temperature after calcination can be rapidly cooled, forming a large number of defects on the surface of the MOF-derived material, which can increase the number of oxygen vacancies on the one hand, and oxygen vacancies are conducive to electron transmission and improve the catalytic effect; on the other hand, it is conducive to increasing the loading amount of the metal, and the MOF-derived material has a strong binding force with the metal and is not easy to fall off, so that the photocatalyst has good stability. The present invention reduces the MOF-derived material loaded with metal ions through reduction treatment, which can promote the reduction of metal ions to form metal elements or clusters. The metal can generate heat when used as a photocatalyst, so that oxygen vacancies and metals can produce photo-thermal effect synergistic catalysis, thereby significantly improving the catalytic effect of the photocatalyst. The results of the embodiment show that the MOF-based derivative composite photocatalyst prepared by the present invention has a photocatalytic degradation rate of 97% within 60 minutes for tetracycline hydrochloride (TC) (with a concentration of 20ppm) under ultraviolet light irradiation of 365nm, a mineralization rate of 95% within 5 hours, and a mineralization reaction rate of 0.6321min -1 It is 2.75 times that of the original TiO2; 56% (concentration of 50ppm) of tetracycline hydrochloride (TC) was degraded within 120min; the degradation rate of RhB reached 99.98% in 50min. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD pattern of NH2-MIL-125(Ti) prepared in the present invention;

[0022] Figure 2 TiO2-Q-Pd prepared in Example 1 of the present invention 2+ , XRD patterns of TiO2-Q-Pd, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2;

[0023] Figure 3 SEM images of NH2-MIL-125 and TiO2-Q-Pd prepared in Example 1 of the present invention, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2, wherein a is NH2-MIL-125, b is TiO2-NC, c is TiO2-Q, d is TiO2-Q-Pd, e is TiO2-NC, and f is TiO2-Q-Pd;

[0024] Figure 4 TEM images of TiO2-Q-Pd prepared in Inventive Example 1, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2, wherein a is TiO2-NC, b is TiO2-Q, c is TiO2-Q-Pd, d is Ti, e is O, and f is Pd;

[0025] Figure 5 TiO2-Q-Pd prepared in Example 1 of the present invention 2+ , TiO2-Q-Pd, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2;

[0026] Figure 6 For the present invention Figure 5 The linear fitting curve of

[0027] Figure 7 TiO2-Q-Pd prepared in Example 1 of the present invention 2+ , TiO2-Q-Pd, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2;

[0028] Figure 8 For the present invention Figure 7 The linear fitting curve of

[0029] Fig. 9 The cyclic test results of TiO2-Q-Pd prepared in Example 1 of the present invention;

[0030] Fig.10 The mineralization rate of TiO2-Q-Pd prepared in Example 1 of the present invention after 1 to 4 cycles of experiments for 5 hours;

[0031] Fig.11 The degradation performance test results of TiO2-Q-Ag prepared in Examples 3 to 8 of the present invention and TiO2-Q prepared in Comparative Example 2 on tetracycline hydrochloride solution are shown. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a MOF-based derivative composite photocatalyst, comprising the following steps:

[0033] (1) calcining the MOF to obtain a MOF-derived material;

[0034] (2) quenching the MOF derivative material obtained in step (1) in a soluble metal salt solution to obtain a MOF derivative material loaded with metal ions;

[0035] (3) The metal ion-loaded MOF-derived material obtained in step (2) is subjected to reduction treatment to obtain a MOF-based derived composite photocatalyst.

[0036] The present invention calcines MOF to obtain MOF-derived materials.

[0037] In the present invention, the MOF preferably includes one or more of Ti-based metal organic framework materials, Co-based metal organic framework materials, Ni-based metal organic framework materials, Fe-based metal organic framework materials and Mn-based metal organic framework materials, and more preferably Ti-based metal organic framework materials. In the present invention, the Ti-based metal organic framework material is preferably one or more of NH2-MIL-125 (Ti), MIL-125, NTU-9 and PCN-22; the Co-based metal organic framework material is preferably one or more of MOF-74, ZIF-67 and ZIF-9; the Fe-based metal organic framework material is preferably one or more of MIL-101, MIL-53 and MIL-88B; the Mn-based metal organic framework material is preferably one or more of MOF-74, Mn-TCPP and nMn-MOF. The present invention uses MOF as a carrier of a photocatalyst, and can form a MOF-derived material with a MOF pore structure after calcination.

[0038] The present invention has no special limitation on the source of the MOF, and any MOF that can be obtained by those skilled in the art can be used.

[0039] In an embodiment of the present invention, the MOF may be NH2-MIL-125(Ti); the preparation method of the NH2-MIL-125(Ti) may be: 2-aminoterephthalic acid, methanol, dimethylformamide and tetrabutyl titanate are mixed, and hydrothermally treated to obtain NH2-MIL-125(Ti).

[0040] In the present invention, the ratio of the mass of 2-aminoterephthalic acid to the volume of methanol, dimethylformamide and tetrabutyl titanate is preferably (0.5-0.6) mg: (2.9-3.1) mL: (6.9-7.1) mL: (335-345) μL, and more preferably 0.54 mg: 3 mL: 7 mL: 340 μL.

[0041] In the present invention, the method for mixing 2-aminoterephthalic acid, methanol, dimethylformamide and tetrabutyl titanate is preferably to mix and dissolve 2-aminoterephthalic acid, methanol and dimethylformamide to obtain a mixed solution, and then add tetrabutyl titanate to the mixed solution and mix evenly.

[0042] In the present invention, the temperature of the hydrothermal reaction is preferably 140-160° C., more preferably 150° C.; the time of the hydrothermal reaction is preferably 23-25 ​​hours, more preferably 24 hours. The present invention forms MOF by hydrothermal reaction.

[0043] In the present invention, after the hydrothermal reaction, the obtained solid is preferably washed and dried to obtain NH2-MIL-125(Ti). In an embodiment of the present invention, the washing reagent may be DMF and / or methanol, the washing times may be 3 times, the drying temperature may be 60°C, and the drying time may be 12 hours.

[0044] The present invention adopts the above method to obtain relatively pure NH2-MIL-125 (Ti).

[0045] In the present invention, the calcination temperature is preferably 400-500°C, more preferably 450°C; the calcination time is preferably 1-3h, more preferably 2h. The present invention can decompose the organic ligands in MOF by calcination, and the formed MOF derivative material has a porous structure. In an embodiment of the present invention, the calcination device can be a muffle furnace, and the calcination atmosphere can be air.

[0046] After obtaining the MOF derivative material, the present invention performs a quenching treatment on the MOF derivative material in a soluble metal salt solution to obtain the MOF derivative material loaded with metal ions.

[0047] In the present invention, the soluble metal salt in the soluble metal salt solution includes one or more of palladium chloride, silver nitrate, chloroauric acid, platinum nitrate, ruthenium nitrate, nickel nitrate and copper nitrate, and is more preferably palladium chloride. The present invention uses the above-mentioned soluble metal salt solution to load the MOF-derived material, and can utilize the interaction between the metal and the MOF-derived material to improve the photocatalytic effect.

[0048] In the present invention, the concentration of the soluble metal salt solution is preferably 0.25 to 1 mmol / L, more preferably 0.5 mmol / L. The present invention controls the concentration of the soluble metal salt solution within the above range, which is more conducive to the uniform distribution of metal ions in the MOF-derived material and controls the loading amount of metal in the MOF-based derived composite photocatalyst.

[0049] In the present invention, the ratio of the mass of the MOF-derived material to the volume of the soluble metal salt solution is preferably 50-150 mg:10-30 mL, more preferably 100 mg:20 mL. The present invention controls the ratio of the mass of the MOF-derived material to the volume of the soluble metal salt solution within the above range, so that the MOF-derived material and the soluble metal salt solution are fully mixed and rapid cooling is achieved.

[0050] In the present invention, the quenching treatment method is preferably to mix and stir the MOF derivative material with a soluble metal salt solution. The present invention can make the MOF derivative material and the soluble metal salt solution uniformly mixed by stirring, so that the MOF derivative material at a high temperature after calcination is quickly cooled, and in the process of cooling, a large number of defects are formed, so that the metal ions are loaded in the MOF derivative material.

[0051] In the present invention, the temperature of the soluble metal salt solution during the quenching treatment is preferably 0-20° C., more preferably 0-5° C. The present invention controls the temperature of the soluble metal salt solution within the above range, which is more conducive to improving the photocatalytic activity of the MOF-based derived composite photocatalyst.

[0052] In the present invention, the quenching time is preferably 1 to 5 minutes, more preferably 3 minutes. The present invention controls the quenching time within the above range, which can rapidly cool down the high-temperature MOF derivative material after calcination, form abundant oxygen vacancies, and increase the loading capacity of metal ions.

[0053] The present invention preferably filters and dries the system obtained by the quenching treatment in sequence to obtain a MOF-derived material loaded with metal ions. The present invention does not specifically limit the operation method of the filtration and drying, and a conventional filtration and drying operation method can be used. In an embodiment of the present invention, the drying temperature can be 100° C., and the drying time can be 12 hours.

[0054] After obtaining the MOF-derived material loaded with metal ions, the present invention performs a reduction treatment on the MOF-derived material loaded with metal ions to obtain a MOF-based derived composite photocatalyst.

[0055] In the present invention, the reduction treatment is preferably performed in a tube furnace.

[0056] In the present invention, the temperature of the reduction treatment is preferably 200-300°C, more preferably 250°C; the time of the reduction treatment is preferably 2-4h, more preferably 3h; the atmosphere of the reduction treatment is preferably a mixture of hydrogen and nitrogen, and the volume ratio of the hydrogen and nitrogen is preferably (6-8): (92-94), more preferably 7: 93. The present invention can reduce the metal ions in the MOF-derived material loaded with metal ions through the reduction treatment.

[0057] The present invention quenches the calcined MOF-derived material in a soluble metal salt solution, and then reduces it to obtain a MOF-based derived composite photocatalyst. The method provided by the present invention is simple to operate and has mild reaction conditions, and can solve the problems of complex operation methods and harsh reaction conditions in the preparation method of MOF-derived materials.

[0058] The present invention also provides a MOF-based derivative composite photocatalyst prepared by the preparation method described in the above technical solution, comprising a MOF-derived material and a metal loaded on the MOF-derived material.

[0059] In the present invention, the MOF-derived material is preferably a product obtained by calcining MOF. The MOF preferably includes one or more of a Ti-based metal organic framework material, a Co-based metal organic framework material, a Ni-based metal organic framework material, a Fe-based metal organic framework material and a Mn-based metal organic framework material, and is more preferably a Ti-based metal organic framework material.

[0060] In the present invention, the mass percentage (loading amount) of the metal in the MOF-based derived composite photocatalyst is preferably 0.5-2%, more preferably 1-1.5%. The MOF-based derived composite photocatalyst provided by the present invention has a high metal loading amount and good photocatalytic activity.

[0061] The present invention also provides the use of the MOF-based derivative composite photocatalyst described in the above technical solution in treating wastewater containing antibiotics.

[0062] In the present invention, the antibiotics preferably include one or more of tetracycline hydrochloride, chlortetracycline, norfloxacin and ciprofloxacin. The photocatalyst provided by the present invention has excellent catalytic activity, so it can be used for catalytic degradation of various antibiotics.

[0063] The present invention has no particular limitation on the method of using the MOF-based derivative composite photocatalyst in treating wastewater containing antibiotics, and any conventional method of using a photocatalyst to catalyze and degrade organic wastewater may be used.

[0064] The present invention can make the MOF-based derivative composite photocatalyst have excellent photocatalytic activity by controlling the preparation method of the MOF-based derivative composite photocatalyst, so that the antibiotics in the organic wastewater can be efficiently degraded.

[0065] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] The preparation method of MOF (NH2-MIL-125 (Ti)) used in the embodiment is as follows: 0.54g of 2-aminoterephthalic acid (NH2-H2BDC) is dispersed in a mixture of 3mL of methanol and 7mL of dimethylformamide and stirred until the solution becomes clear, 340μL of tetrabutyl titanate (TBT) is added and stirred for 30min. The obtained mixed solution is transferred to a 50mL hydrothermal reactor and then heated at 150°C for 24h. The synthesized solid is further washed and purified three times with DMF and methanol, and then vacuum dried at 60°C for 12h to obtain NH2-MIL-125 (Ti);

[0067] The prepared product was tested by XRD. Figure 1 It can be seen that the diffraction peaks at 6.84°, 9.79°, 11.69°, 15.42°, 16.62°, 17.94°, 19.02°, 19.58°, 22.61°, 23.46°, 24.33° and 26.23° correspond to the (101), (002), (211), (220), (310), (103), (222), (312), (213), (400), (004) and (422) planes of NH2-MIL-125, indicating that NH2-MIL-125 has been successfully prepared.

[0068] Example 1

[0069] A method for preparing a MOF-based derivative composite photocatalyst, comprising the following steps:

[0070] (1) placing NH2-MIL-125(Ti) in a muffle furnace and calcining it at 450°C for 2 h in an air atmosphere to obtain a MOF-derived material;

[0071] (2) 100 mg of the MOF derivative material obtained in step (1) was taken out and quickly poured into 20 mL of a 0.5 mmol / L palladium chloride aqueous solution while hot and stirred for 3 min for quenching treatment. After filtering, the mixture was dried at 100 ° C for 12 h to obtain a MOF derivative material loaded with palladium ions (denoted as TiO2-Q-Pd 2+ );

[0072] (3) The palladium ion-loaded MOF-derived material obtained in step (2) was subjected to reduction treatment in a tubular furnace with hydrogen and nitrogen (volume ratio of 7:93) as atmosphere at a temperature of 250° C. for 3 h to obtain a MOF-based derived composite photocatalyst (denoted as TiO2-Q-Pd). The Pd loading was tested to be 0.86%.

[0073] The quenched material prepared in this embodiment was subjected to XRD test. Figure 2It can be seen that the components of the products after calcination of NH2-MIL-125 are all TiO2.

[0074] Example 2

[0075] A method for preparing a MOF-based derived composite photocatalyst, which is different from Example 1 in that the metal salt solution is an aqueous solution of chloroauric acid with a concentration of 0.25 mmol / L, and the remaining steps are the same as Example 1. The obtained MOF-based derived composite photocatalyst is recorded as TiO2-Q-Au, and the Au loading is 0.86%.

[0076] Embodiments 3 to 8

[0077] A method for preparing a MOF-based derived composite photocatalyst, which is different from Example 1 in that the metal salt solution is a silver nitrate aqueous solution with concentrations of 0.9 mmo / L, 2.25 mmo / L, 3.15 mmo / L, 3.6 mmo / L, 4.05 mmo / L, and 4.95 mmo / L, respectively, and the remaining steps are the same as in Example 1. The obtained MOF-based derived composite photocatalyst is recorded as TiO2-Q-Ag, and the Ag loadings are 2%, 5%, 7%, 8%, 9%, and 11%, respectively.

[0078] Comparative Example 1

[0079] A method for preparing a photocatalyst: placing NH2-MIL-125 (Ti) in a muffle furnace, calcining at 450°C for 2 hours in an air atmosphere, and naturally cooling to room temperature to obtain a photocatalyst (referred to as TiO2-NC)

[0080] Comparative Example 2

[0081] A method for preparing a photocatalyst: NH2-MIL-125 (Ti) is placed in a muffle furnace and calcined at 450° C. for 2 hours in an air atmosphere. After the calcination, it is quickly poured into water and stirred for 3 minutes for quenching treatment to obtain a photocatalyst (denoted as TiO2-Q).

[0082] Test Example 1

[0083] (1) SEM images of NH2-MIL-125 and TiO2-Q-Pd prepared in Example 1, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2 Figure 3 It can be seen that the morphology of TiO2 in TiO2-Q-Pd remains basically unchanged, still maintaining the round cake shape of NH2-MIL-125, but the size becomes smaller. Under high-power electron microscope, it can be clearly seen that the surface of TiO2-NC sample is smoother, while the surface of TiO2-Q-Pd sample is rough due to the granularity of loaded metal Pd.

[0084] TEM images of TiO2-Q-Pd prepared in Example 1, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2 Figure 4 It can be seen that the 0.348nm lattice fringes in TiO2-NC conform to the crystal plane (101) of the anatase type. In the quenched sample, the lattice fringes remain unchanged, proving that the crystal phase has not changed. However, due to the quenching process, the edge surface area of ​​the carbon layer of the nanomaterial becomes jagged and full of defects, while the unquenched nanomaterial appears smoother. In addition, after the TiO2-Q-Pd sample is quenched in a palladium chloride solution, the surface of the carbon layer presents a stepped surface with many defects, which may be the result of the synergistic effect of rapid cooling and cation doping. The stepped surface produced by quenching is expected to increase the oxygen vacancy content.

[0085] (2) The pore structures of TiO2-Q-Pd prepared in Example 1, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2 were studied using N2 isotherm measurements. Type I N2 adsorption-desorption curves were shown on NH2-MIL-125(Ti), indicating that NH2-MIL-125(Ti) is a typical microporous material. In addition, the SBET and total pore volume of NH2-MIL-125(Ti) were 989.88 m 2 g -1 and 227.43cm 3 g -1 The TiO2-NC, TiO2-Q and TiO2-Q-Pd materials obtained by calcining and quenching NH2-MIL-125(Ti) in air atmosphere showed type IV adsorption isotherms and obvious H3 hysteresis loops, indicating that the TiO2-NC, TiO2-Q and TiO2-Q-Pd materials were microporous and mesoporous materials. The surface areas of TiO2-NC, TiO2-Q and TiO2-Q-Pd materials were calculated to be 34.253 m 2 ·g -1 、37.268m 2 ·g -1 and 28.383m 2 ·g -1 This indicates that the specific surface area of ​​NH2-MIL-125(Ti) is greatly reduced after calcination. Compared with NH2-MIL-125(Ti), the SBET of TiO2-Q-Pd material decreases rapidly to 28.383 mm 2 ·g -1 , which is attributed to the loss of micropores caused by the collapse of the Ti-MOF framework during calcination.

[0086] The physicochemical parameters of the photocatalysts of NH2-MIL-125(Ti), TiO2-Q-Pd prepared in Example 1, TiO2-NC prepared in Comparative Example 1, and TiO2-Q prepared in Comparative Example 2 are shown in Table 1:

[0087] Table 1 Physical and chemical parameters of each sample

[0088] sample <![CDATA[S a BET (m 2 g -1 )]]> <![CDATA[D b (nm)]]> <![CDATA[V c (cm 3 g -1 )]]> <![CDATA[NH2-MIL-125]]> 989.88 2.3843 227.43 <![CDATA[TiO2-NC]]> 34.253 18.387 7.8698 <![CDATA[TiO2-Q]]> 37.268 15.977 8.5625 <![CDATA[TiO2-Q-Pd]]> 28.383 20.5 6.5211

[0089] In Table 1, S a BET (m 2 g -1 ) is the BET specific surface area; D b is the average pore size. c is the total pore volume measured at P / P0=0.99.

[0090] Application Example 1

[0091] Application of a MOF-based derived composite photocatalyst in the degradation of tetracycline hydrochloride (TC) aqueous solution: the device is a multi-channel photocatalytic system (Perfectlight, white light 5W), and the light source is provided by a single-wavelength ultraviolet LED lamp of 365nm;

[0092] 5 mg of the MOF-based composite photocatalyst prepared in Example 1 was dispersed in 30 mL (20 mg / L) of TC solution; before light irradiation, it was stirred in the dark for 30 min to achieve adsorption and desorption equilibrium; a certain amount of the dispersion was filtered at a certain time interval; the concentration of TC was determined by UV-visible spectrophotometry at the maximum absorption wavelength of 357 nm and the concentration of TOC was determined in a total organic carbon meter. All experiments were repeated three times at room temperature.

[0093] Comparative application example 1

[0094] The difference from Application Example 1 is that the TiO2-Q-Pd prepared in Example 1 is used. 2+ As a photocatalyst, the rest of the operation method is the same as that of Application Example 1.

[0095] Comparative Application Example 2

[0096] The difference from Application Example 1 is that the TiO2-NC prepared in Comparative Example 1 is used as the photocatalyst, and the rest of the operation method is the same as that of Application Example 1.

[0097] Comparative Application Example 3

[0098] The difference from Application Example 1 is that TiO2-Q prepared in Comparative Example 2 is used as the photocatalyst, and the rest of the operation methods are the same as those in Application Example 1.

[0099] Test Example 2

[0100] Photocatalytic degradation performance of TC under single-wavelength ultraviolet light (365 nm) in Application Example 1 and Comparative Application Examples 1 to 3: All catalysts were subjected to a 30-min dark reaction before illumination to achieve adsorption / desorption equilibrium. Figure 5 As shown in the figure, a blank control experiment was first performed. Under ultraviolet light irradiation, tetracycline hydrochloride without catalyst could be photolyzed by 40.4% within 60 min, which was comparable to TiO2-NC (91.1%), TiO2-Q (92.6%) and TiO2-Q-Pd 2+ Compared with the TiO2-Q-Pd composite material (97%), the TiO2-Q-Pd composite material has the best TC removal effect. Figure 6 Through the linear fitting of TC degradation time and -ln(C0 / C), without adding catalyst, TiO2-NC, TiO2-Q, TiO2-Q-Pd 2+ The apparent rate constants K of TiO2-Q-Pd and TiO2-Q-Pd were 0.00859min -1 、0.04028min -1 、0.04288min -1 、0.05333min -1 and 0.06186min -1 .

[0101] Since the TC degradation process will produce more complex intermediates, and even more toxic and unstable products, its mineralization (the final products are small molecules and harmless substances such as CO2 and H2O) was further studied. Before illumination, all catalysts were subjected to a 30-min dark reaction to achieve adsorption / desorption equilibrium. Figure 7 As shown, a blank control experiment was first conducted. Compared with the degradation situation, the mineralization rate of TC without catalyst addition was 0% within 6 hours, that is, no mineralization occurred. This experiment proves that TC can be photolyzed into other products by ultraviolet light, but the final product is not small molecular harmless substances such as CO2 and H2O. TiO2-NC, TiO2-Q, TiO2-Q-Pd 2+ The mineralization rates of TiO2-Q-Pd and TiO2-Q-Pd at 6h were 70.5%, 77.2%, 86.4% and 95% respectively. Among them, the TiO2-Q-Pd composite material has the best mineralization effect on TC, which can reach 95% after 5h of UV irradiation and then reach equilibrium. Figure 8 Through the linear fitting of TC mineralization time and -ln(TOC0 / TOC), TiO2-NC, TiO2-Q, TiO2-Q-Pd 2+ The apparent rate constants K values ​​of TO2-Q-Pd and TO2-Q-Pd are 0.2292, 0.2906, 0.4232 and 0.6321 min, respectively. -1 .

[0102] In order to explore whether the prepared TiO2-Q-Pd composite photocatalyst is stable, a cyclic test experiment was carried out on the TiO2-Q-Pd sample with the best photocatalytic degradation and mineralization of TC. In order to minimize sample loss in the collection of TiO2-Q-Pd samples, after the removal of TC, wait for the catalyst to precipitate and then absorb the remaining reaction liquid. After adding new TC solution, continue the above photocatalytic degradation and mineralization TC experiment. Under the premise of unchanged experimental conditions, 4 cyclic experiments of degradation and mineralization TC solution tests were carried out. The experimental results are as follows: Fig. 9 As shown in the figure, the degradation rates of the 1st to 4th cycle experiments were 97%, 95.7%, 93.2% and 91% for 60 min, respectively. Fig.10 The 5h degradation mineralization rates of the 1st to 4th cycle experiments were 95%, 94.2%, 92.7% and 91% respectively. It can be seen that through the 4 repeated utilization experiments, the degradation and mineralization efficiency of the TiO2-Q-Pd sample did not change much each time it was degraded. After completing the 4 cycle experiments, it was found that the degradation and mineralization efficiency was only slightly lower than that of the first experiment. It is speculated that this slight change was caused by the loss of the amount of catalyst during the reaction. From this, we can conclude that the prepared TiO2-Q-Pd composite catalyst has good chemical stability and high photocatalytic degradation and mineralization TC efficiency.

[0103] Application Examples 2 to 7

[0104] Application of a MOF-based derivative composite photocatalyst in the degradation of tetracycline hydrochloride aqueous solution: the device is a multi-channel photocatalytic system (Perfectlight, white light 5W), and the light source is provided by an LED lamp with a single ultraviolet wavelength of 365nm;

[0105] 100 mg of TiO2-Q-Ag prepared in Examples 3 to 8 and TiO2-Q prepared in Comparative Example 2 (Ag loading is 0%) were added to 100 mL of tetracycline hydrochloride solution (50 ppm), and magnetic stirring was performed for 30 min under completely dark conditions to allow the catalyst and tetracycline hydrochloride solution in the reaction system to reach an adsorption equilibrium state. The solution concentration measured at the end of the dark adsorption reaction for 30 min was taken as C0. After turning on the light source, 4 mL of the suspension was taken from the reaction solution every 20 min and centrifuged (4000 rpm, 8 min), and then filtered through a 0.22 μm filter to remove the suspended photocatalyst particles in the solution. Finally, a UV-visible spectrophotometer was used to measure the absorbance of the tetracycline hydrochloride solution at a wavelength of 354 nm to determine its concentration C t , and calculate the degradation rate, and use the degradation rate to determine the photocatalytic performance.

[0106] Degradation rate = [(C t-C0) / C0]×100%, where C0 is the mass concentration of tetracycline hydrochloride solution at the end of the dark reaction, mg / L; C t is the mass concentration of tetracycline hydrochloride solution at the beginning of the light reaction, mg / L.

[0107] The result is as follows Fig.11 As shown. Fig.11 It can be seen that under the same conditions, different TiO2-Q-Ag synthesized by changing the loading amount of silver ions, among which the Ag loading amount of 8% showed the fastest reaction rate and the highest degradation rate. The reason is that on the one hand, when the Ag loading amount is 8%, the catalyst has higher light absorption performance, providing more photogenerated carriers in the catalytic reaction. On the other hand, when the Ag loading amount is 8%, the catalyst is conducive to electron-hole separation, so that more reaction active centers are generated, thereby being able to efficiently degrade tetracycline hydrochloride. In addition, from Fig.11 It can be seen that when Ag + When the content of Ag is too high, the photocatalytic performance of the synthesized material decreases. It is inferred that the active sites on the surface of TiO2-Q-Ag are occupied by too much Ag. + covered, its photocatalytic performance is reduced.

[0108] From the above results, it can be seen that the MOF-based composite photocatalyst prepared by the present invention has an excellent catalytic degradation effect on tetracycline. This is because the quenching produces a disordered step surface with abundant oxygen vacancy defects at the atomic level, which accelerates the separation of electron holes. The carbon coating acts as a barrier layer to prevent O v The carbon matrix has good electrical conductivity, which allows the electrons generated by the ultraviolet light irradiation catalyst to move freely on the surface of the carbon-based skeleton. All of these are beneficial to the catalytic efficiency of the photocatalyst. The oxidative free radicals ·OH, ·O generated by the TiO2-Q-Pd composite catalyst 2- and h + They each play their own role in the degradation and mineralization of TC, thus showing significantly superior photocatalytic activity and high mineralization efficiency in the liquid phase oxidation of TC under ultraviolet light. Using readily available MOFs as starting materials, a catalyst with excellent photocatalytic performance can be obtained through simple quenching and reduction.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a MOF-based derivative composite photocatalyst, comprising the following steps: (1) calcining the MOF to obtain a MOF-derived material; (2) quenching the MOF derivative material obtained in step (1) in a soluble metal salt solution to obtain a MOF derivative material loaded with metal ions; (3) The metal ion-loaded MOF-derived material obtained in step (2) is subjected to reduction treatment to obtain a MOF-based derived composite photocatalyst.

2. The preparation method according to claim 1, characterized in that: The MOF in step (1) includes one or more of a Ti-based metal organic framework material, a Co-based metal organic framework material, a Ni-based metal organic framework material, a Fe-based metal organic framework material and a Mn-based metal organic framework material.

3. The preparation method according to claim 1, characterized in that: In the step (1), the calcination temperature is 400-500° C., the calcination time is 1-3 hours, and the calcination atmosphere is air.

4. The preparation method according to claim 1, characterized in that: The soluble metal salt in the soluble metal salt solution of step (2) includes one or more of palladium chloride, silver nitrate, chloroauric acid, platinum nitrate, ruthenium nitrate, nickel nitrate and copper nitrate.

5. The preparation method according to claim 1 or 4, characterized in that: The concentration of the soluble metal salt solution is 0.25-1 mmol / L.

6. The preparation method according to claim 1, characterized in that: During the quenching treatment in step (2), the temperature of the soluble metal salt solution is 0 to 20° C.; and the quenching treatment time is 1 to 5 minutes.

7. The preparation method according to claim 1, characterized in that: The temperature of the reduction treatment in step (3) is 200-300° C.; the time of the reduction treatment is 2-4 hours; and the atmosphere of the reduction treatment is a mixture of hydrogen and nitrogen.

8. The MOF-based derivative composite photocatalyst prepared by the preparation method according to any one of claims 1 to 7, comprising a MOF-derived material and a metal supported on the MOF-derived material.

9. The MOF-based composite photocatalyst according to claim 8, characterized in that: The mass percentage of the metal in the MOF-based derived composite photocatalyst is 0.5-2%.

10. Use of the MOF-based derivative composite photocatalyst according to any one of claims 8 to 9 in treating wastewater containing antibiotics.

Citation Information

Cited By

  • In2O3 / ZnWO4 composite photocatalytic material as well as preparation method and application thereof

    CN120054652A